Identifying High Performing Symmetric Key Algorithms in Transferring Data into Cloud - Sharma, Ashok (International Journal of Computer Sciences and Engineering, 2025)
The drastic amount of data is transferred into public cloud at every moment and securing data while transferring into cloud has become a tradition and in this paper we present scope of improvement for using optimized symmetric key algorithm for cloud environment. After careful investigation AES, 3DES, RC6, Twofish, Blowfish algorithms, In this paper, we proposed an approach to select optimized algorithm for deciding the use of efficient algorithm in cloud depending upon the outcomes of investigations carried. The future work can be carried out in the direction of replacement of conventional key expansion routine with the genetic concept routine in the identified algorithm.